Nanoscopy with more than 100,000 'doughnuts' - Chmyrov, A; Keller, J; Grotjohann, T; Ratz, M; D'Este, E; Jakobs, S; Eggeling, C; Hell, S (2013)
We show that nanoscopy based on the principle called RESOLFT (reversible saturable optical fluorescence transitions) or nonlinear structured illumination can be effectively parallelized using two incoherently superimposed orthogonal standing light waves. The intensity minima of the resulting pattern act as 'doughnuts', providing isotropic resolution in the focal plane and making pattern rotation redundant. We super-resolved living cells in 120 μm × 100 μm-sized fields of view in <1 s using 116,000 such doughnuts. © 2013 Nature America, Inc. All rights reserved.